Protection of Chicken Embryos by Viridans Streptococci Against the Lethal Effect of Staphylococcus aureus - Aly, Raza (1974)
Chicken embryos were used to investigate the mechanism by which viridans streptococci inhibit the growth of pathogenic staphylococci. Ten-day-old embryonated eggs were infected allantoically. At a concentration of 1.8 × 10(2) colony-forming units (CFU) of viridans streptococci, the percentage of fatalities was less than 10%. There was 80% fatality with 8 × 10(1) CFU of Staphylococcus aureus strain 502A and 100% when a 100-fold increase in concentration was used. An inoculum size of 10(2) to 10(3) CFU of viridans streptococci was chosen to protect the embryos against the lethal effect of strain 502A when challenged 24 h later. The survival after challenging at 4 days was 93% in protected eggs and 37% in unprotected eggs. Chicken embryos receiving heat-killed viridans and challenged with strain 502A when examined after 4 days did not demonstrate a protective effect. This protection of embryonated eggs could not be transferred by administration of sterile filtrate of allantoic fluid in which protecting strain was grown. The experimental infection of embryonated eggs has demonstrated that prior allantoic infection with viridans streptococci affords significant protection against subsequent challenge with virulent staphylococci.